CURRENT ACADEMIC LECTURE - Belyaeva, E.N. (World of Medicine and Biology, 2015)
Academic lecture is regarded as one of the oldest organizational forms of education. The advantages and disadvantages of the lecture were analyzed. The functions and principles of lecture were defined. Theoretical and psycho-pedagogical requirements of a modern academic lecture were differentiated. The necessity of interactive methods usage during the lectures, that allow not only to abandon presentation of provided knowledge to the students, but also to create conditions for dialogue and active interaction between lecturer and student is focused on. In conclusion the author contends that the drawbacks of academic lecture, which are traditionally identified by resear-chers, can be eliminated by means of constant develop-ment and improvement of lecturer’s methodical, communicative and professional competencies.
Keywords: academic lecture; the advantages and disadvantages of lecture; functions and principles of lecture; interactive techniques